2009
DOI: 10.1007/s12325-009-0056-z
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and costs of patients with persistent asthma treated with beclomethasone dipropionate hydrofluoroalkane or fluticasone propionate

Abstract: Results indicate that receipt of BDP-HFA, compared with receipt of FP, is associated with a decreased probability of ER visits or asthma-related ER visits and higher odds of reaching a medical possession ratio threshold of 50% or 75%. Receipt of BDP-HFA was also associated with lower total drug costs and lower total medical costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…A number of observational studies and historical matched cohort analyses have recently been published comparing the outcomes and cost of treatment with small versus standard size particle ICS in patients with asthma [ 43 46 ]. In general, the studies found that asthma treatment outcomes were similar or better with small size particle ICS (BDP) compared with standard size particle ICS (FP).…”
Section: Discussionmentioning
confidence: 99%
“…A number of observational studies and historical matched cohort analyses have recently been published comparing the outcomes and cost of treatment with small versus standard size particle ICS in patients with asthma [ 43 46 ]. In general, the studies found that asthma treatment outcomes were similar or better with small size particle ICS (BDP) compared with standard size particle ICS (FP).…”
Section: Discussionmentioning
confidence: 99%
“… 32 More recently, in a 1-year US database study, significantly lower drug and total medical costs and fewer emergency department visits were reported with extrafine beclomethasone compared with fluticasone for adults and children (5–64 years old) with persistent asthma. 33 Prior studies comparing extrafine beclomethasone and fluticasone were short-term (3–12 weeks) randomised trials that did not evaluate cost-effectiveness. 34 …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the current standard treatment of asthma with ICSs is not available in countries in which basic inhaled medications containing ICSs are not available to many patients because of their high cost [75,88]. At the same time, the cost of basic inhaled medications containing corticosteroids is still not decreasing [92][93][94][95]. At the same time, the incidence of asthma is increasing and the income of the population in many countries remains low [96].…”
Section: Resultsmentioning
confidence: 99%